2016
DOI: 10.1007/978-3-319-45457-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Blood-Derived Stem Cells: In Vitro and In Vivo Characterization of Functional Effects

Abstract: Accumulating evidence has demonstrated that menstrual blood stands as a viable source of stem cells. Menstrual blood-derived stem cells (MenSCs) are morphologically and functionally similar to cells directly extracted from the endometrium, and present dual expression of mesenchymal and embryonic cell markers, thus becoming interesting tools for regenerative medicine. Functional reports show higher proliferative and self-renewal capacities than bone marrow-derived stem cells, as well as successful differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Until recently, the most common way to isolate hMESCs was to take biopsy of endometrial tissue through a cervix [7,8]. In 2007-2008, two independent research groups isolated stem cells from desquamated endometrium collected from menstrual blood [4,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, the most common way to isolate hMESCs was to take biopsy of endometrial tissue through a cervix [7,8]. In 2007-2008, two independent research groups isolated stem cells from desquamated endometrium collected from menstrual blood [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007-2008, two independent research groups isolated stem cells from desquamated endometrium collected from menstrual blood [4,9]. Importantly, cells obtained from menstrual blood are morphologically and functionally similar to cells directly extracted from the endometrium [8]. hMESCs display all the necessary characteristics inherent to the stem cells of mesenchymal origin [4,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they demonstrated that MenSCs have the shortest population doubling time, the highest clonogenic efficacy, and the largest number of in vitro passages before becoming senescent [23]. More recently, MenSCs have been extensively characterized in vitro and in vivo and their potential for cellular therapy has been described [2426]. Altogether, these features point out that menstrual blood represents an efficient and ethically accepted source of MSCs for clinical treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of MenSCs has been applied to the treatment of multiple sclerosis, Duchenne muscular dystrophy, and more recently, heart failure and liver cirrhosis (reviewed in [26]). Here, we propose the use of MenSCs as cell carriers for OAdv and cancer treatment.…”
Section: Introductionmentioning
confidence: 99%